Surgical lens extraction with vitrectomy in patients with angle-closure glaucoma - Kamińska, Anna; Romaniak, Agnieszka; Izdebska, Justyna; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Closed angle glaucoma is a neurodegenerative disease, resulting from anatomical predisposition, which without appropriate treatment results in irreversible blindness. During intraocular operations in this group of patients, more often than in the general population, severe complications that endanger vision occur. This article presents a surgical technique that combines phacoemulsification of the cataract with partial vitrectomy through the flat part of the ciliary body. In some patients it may act as an glaucoma treatment, eliminating the factors conducive to closing the filtration angle. Its application allows for safe lens replacement under conditions of increased intraocular pressure in patients with very shallow anterior chamber.